Analisis Makna Konotatif Pada Kumpulan Lagu Album Daun Jatuh - Ningsih, Dinda Tiara Wia (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
The background of This research because the assumption that connotative meaning is difficult to understand, but it is inversely proportional to the reality. This can be seen in the collection of songs in the album of fallen leaves which contain several connotative meanings, but the number of listeners can reach more than 29 million and is still growing. The purpose of this study was to analyze and explain the connotative meaning of positive and negative feelings in a collection of songs in the album of fallen leaves. This research uses the song lyrics contained in the album of fallen leaves as an object to get some data. The method used by the researcher is the Content Analysis Method. Based on the results of the research on the connotative meaning of the collection of fallen leaves album songs, several positive category and negative category connotative meanings were found. There are 5 positive connotative meanings and 3 negative connotative meanings. Based on this data, it can be concluded that the connotative meaning used by fallen leaves in each of the songs has positive and negative values.